Facile One-Pot Synthesis of Self-Assembled Folate-Biotin-Pullulan Nanoparticles for Targeted Intracellular Anticancer Drug Delivery. (27th March 2016) - Wang, Ming; Huang, Meiling; Wang, Jianting; Ye, Mingquan; Deng, Yan; Li, Honghao; Qian, Wensi; Zhu, Bolin; Zhang, Yao; Gong, Renmin
Abstract : The self-assembled folate-biotin-pullulan (FBP) nanoparticles (NPs) were prepared by facile one-pot synthesis and their physicochemical properties were characterized. The self-assembled FBP NPs were used as an anticancer drug nanocarrier entrapping doxorubicin (DOX) for targeting folate-receptors-overexpressing cancer cells. The identification of prepared NPs to folate-receptor-expressing cancer cells (KB cells) was affirmed by cell viability measurement, folate competition test, and flow cytometric analysis. Compared with the naked DOX and DOX/BP NPs, the DOX/FBP NPs had lower IC50 value compared to KB cells as a result of the folate-receptor-mediated endocytosis process. The cytotoxicity of DOX/FBP NPs to KB cells could be inhibited competitively by free folate. The cellular intake pattern of naked DOX and drug-loaded NPs was identified by confocal laser scanning microscopy (CLSM) observation and the higher cellular uptake of drug for DOX/FBP NPs over naked DOX was observed. The prepared FBP NPs had the potential to be used as a powerful carrier to target anticancer drugs to folate-receptor-expressing tumor cells and reduce cytotoxicity to normal tissues.